Control frameworks for transactive energy storage services in energy communities. (January 2023) - Mignoni, Nicola; Scarabaggio, Paolo; Carli, Raffaele; Dotoli, Mariagrazia
Abstract: Recently, the decreasing cost of storage technologies and the emergence of economy-driven mechanisms for energy exchange are contributing to the spread of energy communities. In this context, this paper aims at defining innovative transactive control frameworks for energy communities equipped with independent service-oriented energy storage systems. The addressed control problem consists in optimally scheduling the energy activities of a group of prosumers, characterized by their own demand and renewable generation, and a group of energy storage service providers, able to store the prosumers' energy surplus and, subsequently, release it upon a fee payment. We propose two novel resolution algorithms based on a game theoretical control formulation, a coordinated and an uncoordinated one, which can be alternatively used depending on the underlying communication architecture of the grid. The two proposed approaches are validated through numerical simulations on realistic scenarios. Results show that the use of a particular framework does not alter fairness, at least at the community level, i.e., no participant in the groups of prosumers or providers can strongly benefit from changing its strategy while compromising others' welfare. Lastly, the approaches are compared with a centralized control method showing better computational results. Highlights: Two innovative transactive control frameworks for energy storage services are defined. The considered system includes prosumers and energy storage service providers. The resolution algorithms are based on a game theoretical formulation. The transactive control frameworks are numerically validated on realistic scenarios. Results show the effectiveness and scalability of the proposed control approaches.